Fatores influenciadores da transparência pública nas capitais brasileiras - Paula, Silvia Helena Soares de (2024)
Considering the growing global interest in transparency - which has been regulated by legal frameworks over the past decades -, it is noticed that there exists a gap between theory and practice in this scenario. From this perspective, this research sought to investigate factors that influence active transparency in Brazilian capitals, considering their socioeconomic and demographic conditions, from the perspective of public choice theory. For this study, a Center for Studies on Administrative Transparency and Public Interest Communication’s (NETACIP) article at University of São Paulo Law School (FDUSP) from 2021-2022 was assessed, using a data sample of 26 Brazilian state capitals. Its Transparency Ranking data was taken into account as a dependent variable in the current evaluation. Considering independent variables, this study included socioeconomic and geographic aspects such as the Human Development Index (HDI), Basic Education Development Index (IDEB), Enrollment Rate (6 to 10 years), GDP per capita (R$/inhabitant), Population, Infant Mortality, Adequate Sanitary Sewerage Rate, and Industry Participation Rate. The current project was accomplished considering these objectives: (i) identify the main indicators of active public transparency and (ii) explore significant relationships between the level of transparency in Brazilian capitals. Through the two applied multiple linear regression models, it was observed that the increase in GDP per capita, HDI, and IDEB is associated with greater transparency in Brazilian capitals. Although the initial analysis (model 1) did not identify a statistically significant relationship between the explanatory variables and transparency, refining the analysis in model 2 made this relationship evident. The results suggest that, although small, advances in transparency contribute to strengthening the democratic system. Although we cannot yet claim to have achieved the desired effects for Brazilian democracy, each step towards transparency represents significant progress. During the research, some limitations were observed. One of them was the difficulty in obtaining more updated data of indicators in the surveyed capitals, with state’s data usually being more up-to-date. Additionally, the sample size was identified as a limitation, hindering more comprehensive analyses.